Drivers of Buy Now Pay Later (BNPL) Adoption in Emerging Markets: A Qualitative Exploration of Shopee PayLater Users in Bogor City, Indonesia - El Hasan, Sawqi Saad (JAKI : Jurnal Akuntansi, 2025)
This study investigates the factors driving the adoption of Shopee PayLater, a "buy now, pay later" fintech service, among residents of Bogor City, Indonesia. Using a qualitative approach, data were collected through semi-structured interviews with 13 active users across sub-districts within Bogor. Thematic analysis revealed four key factors: ease of process, promotional incentives, installment flexibility, and product variety. These findings align with existing literature on fintech adoption, emphasizing convenience and accessibility, while also highlighting the unique influence of promotional strategies in price-sensitive emerging markets. The study contributes to understanding consumer behavior in emerging fintech markets and offers practical insights for policymakers and fintech developers to enhance financial inclusion while mitigating risks associated with potential over-indebtedness.